(NwSADNIKI tXMY (B:s (NpERWAQ PE^ATX (B: [(NrOMAN(B] /s - (NkUATX\(B, (NaNHELX DEs ((NsANKT(B-(NpETERBURG (B;s (NmOSKWA (B:s (NnEWA(B,s, 2005)
(NzNAEM LI MY(B, (N^TO TAKOE tXMA(B? (N~ISTOE SERDCE INTUITIWNO WYBIRAET sWET(B. (NnO MOVET LI ONO PROTIWOSTOQTX ZLU(B, (NNE ZNAQ(B, (N^TO \TO (B- (NtXMA(B? (NsU]ESTWUET PRORO^ESTWO tEMNYH MAGOW O sWQ]ENNOM kOPXE(B. (NpO PREDANI@(B, (N\TIM KOPXEM BYL PRONZEN NA RASPQTII iISUS hRISTOS(B.s
Keywords: (NrUSSKAQ LITERATURA (B- (NS SER(B. 50-(NH GG(B. 20 (NW(B.s; (NfANTASTI^ESKIE I MISTI^ESKIE ROMANY(B, (NPOWESTI(B, (NRASSKAZY(B. (NrOMANY UVASOWs